Kontribusi Komunitas Save Mugo Melalui Pemberdayaan Ekonomi Kreatif Hutan Mangrove - Munah Herawati; Tantan Hermansyah (UIN Siber Syekh Nurjati Cirebon, 2020)
Â AbstractThe mangrove forest area in Muara Gembong Bekasi has benefits for the area and the surrounding community. However, along with economic pressure from large investors, many mangrove forests have been converted into commercial areas such as ponds. As a result, some of the residents are displaced or have lost their livelihoods. Seeing this problem, the presence of the Save Mugo Community, a community group that cares about the environmental rescue movement, is quite helpful for the community to overcome several problems in this region. This study is a long observation to see how the community movement, which in this case is represented by the Save Mugo Community, in overcoming problems in their environment; as well as seeing the impact of this movement on the lives of the community partners of the program. The results of this study indicate that the contributions made by the Save Mugo Community are: (1) environmental empowerment while at the same time endeavoring to conserve the mangrove forest ecosystem; (2) empowerment of ecotourism areas; and (3) creative economy empowerment, which is a continuation of ecotourism empowerment.AbstrakKawasan hutan mangrove di Muara Gembong Bekasi memiliki manfaat bagi daerah tersebut dan masyarakat sekitar. Namun, seiring dengan tekanan ekonomi dari investor besar, banyak hutan mangrove telah diubah menjadi area komersial seperti kolam. Akibatnya, beberapa warga mengungsi atau kehilangan mata pencaharian. Melihat permasalahan ini, kehadiran Komunitas Save Mugo, kelompok masyarakat yang peduli dengan gerakan penyelamatan lingkungan, cukup membantu masyarakat untuk mengatasi beberapa permasalahan di wilayah ini. Penelitian ini merupakan pengamatan panjang untuk melihat bagaimana pergerakan masyarakat, yang dalam hal ini diwakili oleh Komunitas Save Mugo, dalam mengatasi permasalahan di lingkungannya; serta melihat dampak dari gerakan ini terhadap kehidupan mitra masyarakat dari program tersebut. Hasil penelitian ini menunjukkan bahwa kontribusi yang diberikan oleh Komunitas Save Mugo adalah: (1) pemberdayaan lingkungan hidup sekaligus berupaya melestarikan ekosistem hutan mangrove; (2) pemberdayaan kawasan ekowisata; dan (3) pemberdayaan ekonomi kreatif, yang merupakan kelanjutan dari pemberdayaan ekowisata.Â